A review on biological matrices and analytical methods used for determination of drug of abuse - Nikhil Mali, Manisha Karpe, Vilasrao Kadam (Journal of Applied Pharmaceutical Science)
Drug addiction is a chronic disease with a potential for fatality if not treated. The drugs with potential for abuse are mostly psychoactive drugs. Serious widespread medical and health consequences associated with drug abuse involve neurotoxicity, cardiovascular complications, impairment of the immune system function, and many other physiological effects. Illicit drug use remains the second most common mode of HIV infection. Various analytical techniques and number of biological matrices has been used for the detection of drug of abuse in cases such as drug addiction, driving under influence of drugs, neonatal drug exposure in case of drug abuse by pregnant women etc. Urine and blood sample remain the most widely used conventional biosample for the detection of drug of abuse. Various other alternative biological matrices such as saliva, hair, nails, tears and meconium have also been used for the same purpose. Number of analytical techniques such as liquid chromatography with mass spectrometry (LC-MS) and LC with tandem MS (LC-MS2), enzyme-linked immunosorbent assay (ELISA), radioimmunoassay (RIA), electrospray ionization Time-of- Flight mass spectrometry (ESI-TOF), combination of ultra-performance liquid chromatography (UPLC) and TOF, fluorescence polarization immunoassay (FPIA) and enzyme multiplied immunoassay technique (EMIT) have been used for the detection of drugs of abuse in above mentioned biosamples. This review summarizes the conventional as well as alternative biological matrices and various analytical techniques used for the determination of drugs of abuse.
Keywords: MTCT, TRIAGE, HAIRVEQ, Solid phase extraction, liquid-liquid extraction, Fluorescence polarization immunoassay.